The real-world safety profile of ranolazine: pharmacovigilance analysis of the FAERS database - Wen, Zujun; Liu, Xiang; Yi, Yanbin; Lin, Gengliang; Liu, Peng; Zhang, Tingting (Frontiers in Pharmacology, 2025)
BackgroundRanolazine, a piperazine derivative, is used as a second-line treatment for individuals with stable or poorly managed chronic angina as well as for those whose chronic angina is not improving with other medications. However, there is still a lack of real-world evidence on the long-term safety of its adverse events (AEs), which calls for constant supplementation.MethodsThis study conducted disproportionality analysis to evaluate the safety of ranolazine in clinical practice by utilizing data from the FDA Adverse Event Reporting System (FAERS). Reporting Odds Ratio, Proportional Reporting Ratio, Multi-item Gamma Poisson Shrinker and Bayesian Confidence Propagation Neural Network were used to identify signals of possible adverse events linked to ranolazine. Additionally, the Weibull distribution was implemented to simulate how the frequency of adverse events changed over time.ResultsPositive signals were found for adverse events listed on the medication label, including dizziness, nausea, asthenia, constipation, headache, palpitations, tinnitus, abdominal pain, dry mouth, vomiting, peripheral edema, dyspnea and hypotension. Additionally, potential side effects not included on the label were also identified, including chest pain, cardiac disorder, electrocardiogram qt prolonged, hypertension, seizure, tremor, atrial fibrillation, coronary artery disease, pulmonary embolism, myoclonus and myocardial infarction. The significance of tracking adverse events was underlined, especially during the first month after the start of treatment.ConclusionOur study has confirmed certain known adverse effects and identified other potential hazards by providing preliminary safety data on the practical use of ranolazine. The results present vital safety information for physicians prescribing ranolazine. Notably, this study only identifies safety signals and does not establish causal relationships between ranolazine and the observed adverse events.